A escola do trabalho a partir do pensamento gramsciano: um projeto formativo no terreno da luta de classes - Lima, Patrícia Oliveira (2021)
The present dissertation consists in tracking Antonio Gramsci's reflections and conceptions about a possible school of labor; considering his social and political life registered in his thought and work from the perspective of a project of human emancipation and through the relationship between theory and practice. We have chosen to recompose the whole historical and social scenario that made Gramsci think about a possible labor school. Among the scenarios, we will have the Southern Question (Risorgimento); the Vatican Question and the Protestant Reformation, which we find in his journalistic writings. Thus, we trace a path to better analyze some influences of the Russian Revolution and the politics exercised by Vladimir I. Ulyanov. We conducted some considerations about Russian pedagogy with the following philosophers: Nadejda K. Krupskaia and Moisey M. Pistrak. The research is eminently bibliographical in nature. The methodology is referenced by some Gramscian and Marxian classics and their respective interpreters: Del Roio (2006), Oliveira (2013), Simionatto (2011) and some Marxists such as Konder (2008), Rabelo (2016), Netto (2011) etc. Furthermore, the Marxist analysis that we find in the writings of Karl Marx (2010) did not develop a theory on education, but this complex pervades his studies and his contributions that help us understand the educational process placed in the antagonistic struggles between classes. As a result, we realize that the model of the Soviet labor school thought by Gramsci was not materialized in Italy.